Long-Term Stability of Hydromorphone in Human Plasma Frozen at-20 degrees C for Three Years Quantified by LC-MS/MS - Wehrfritz, Andreas; Schmidt, Stefanie; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (International Journal of Analytical Chemistry, 2022)
The long-term stability of drugs under normal laboratory storage conditions (-20 degrees C) for years is important for research purposes, clinical re-evaluation, and also for forensic toxicology. To evaluate the stability of the analgesic opioid hydromorphone, 44 human frozen plasma samples of a former clinical trial were reanalyzed after at least three years. Blood samples were disposed using solid-phase extraction with an additional substitution of stable isotope labelled hydromorphone as an internal standard. Hydromorphone concentrations were determined by ultra-performance liquid chromatography (UPLC) with gradient elution, followed by tandem mass spectrometry with electrospray ionization. Calibration curves demonstrated linearity of the assay in the concentration range of 0.3-20 ng/mL hydromorphone. The limit of detection of the hydromorphone plasma concentration was 0.001 ng/mL, and the lower limit of quantification was 0.3 ng/mL. Intra- and interassay errors did not exceed 16%. The percentage deviation of the measured hydromorphone plasma concentrations between the reanalysis and the first analysis was -1.07% +/- 14.8% (mean +/- SD). These results demonstrate that hydromorphone concentration in human plasma was stable when the samples were frozen at -20 degrees C over three years. This finding is of value for re-evaluations or delayed analyses for research purposes and in pharmacokinetic studies, such as in forensic medicine.
CRIS-Team WoS Importer:2022-07-29

Long-term stability of sufentanil quantified by UPLC-MS-MS in human plasma frozen for 11 years at -20°C. - Wehrfritz, Andreas; Schmidt, Stefanie; Ihmsen, Harald; Schüttler, Jürgen; Jeleazcov, Christian (Journal of Analytical Toxicology, 2025)
The long-term stability of drug concentrations in human plasma samples, when stored under normal laboratory conditions over several years, is important for research purposes and clinical re-evaluation, and forensic toxicology. Fifty human plasma samples from a former clinical trial were re-analyzed after storage at -20°C for 11 years. Plasma samples were extracted using solid-phase extraction. Isotope labeled sufentanil-d5 was used as internal standard. Sufentanil plasma concentrations were determined by ultra-performance liquid chromatography with gradient elution, followed by tandem mass spectrometry with electrospray ionization. The linear dynamic range was 25-2500 pg/mL, the limit of detection was 10 pg/mL, and the lower limit of quantification was 25 pg/mL. Intra- and inter-assay error did not exceed 6%. The deviation of the measured sufentanil plasma concentrations between the re-analysis and the first analysis was -63 ± 14% (mean ± SD). Therefore, sufentanil concentrations in human plasma were not stable in samples frozen at -20°C over 11 years.
EVALuna2:582596

Quantification of Remimazolam Besylate (CNS7056B) and Its Metabolite (CNS7054X) by LC-MS/MS in Human Plasma Using Midazolam-d4 Maleate as Internal Standard - Schmidt, Stefanie; Krajinovic, Ljubica; Mertens, Christian; Schramm, Lisa; Schüttler, Jürgen; Fechner, Jörg (Journal of Chromatographic Science, 2022)
A new assay was developed to measure the concentration of remimazolam besylate (CNS7056B) and its major carboxylic acid metabolite (CNS7054X) in human plasma. For this new assay method, midazolam-d4 maleate was used as an internal standard. After setting up a previously described assay method, using CNS7056-d4 and CNS7054-d4 as internal standards, analytical results of both methods were compared. For the new analytical method, ultra-high-performance liquid chromatography (UHPLC) with tandem mass spectrometry was applied. A purification method, using solid phase extraction, was developed and validated. The chromatographic separation of the analytes was achieved with a mobile phase gradient using a Water Acquity (TM) UHPLC-System. The Kinetex (TM) biphenyl 50 x 2.1 mm UHPLC column was used with a particle diameter of 1.7 mu m (Phenomenex, Germany). A measuring range of 0.6-2,000 ng/mL for CNS7056B and of 6-20,000 ng/mL for CNS7054X could be achieved with this new assay. The lower limit of quantification was 0.6 ng/mL for CNS7056B and 6 ng/mL for CNS7054X. The assay was validated according to US Food and Drug Administration guidelines. The new method showed an accuracy of 96.9-110.4% and a precision of 2.1-6.7% for both analytes.
CRIS-Team WoS Importer:2022-12-23